Apneustic anesthesia ventilation improves pulmonary function in anesthetized bottlenose dolphins (Tursiops truncatus) - Le-Bert, Carolina R.; Bukoski, Alex; Downs, John; Hodgson, David S.; Thombs, Lori; Ridgway, Sam H.; Bailey, James (Frontiers in Veterinary Science, 2024)
Use of mechanical ventilation during general anesthesia is a necessary practice in the anesthetization of small cetaceans as spontaneous ventilation fails to provide adequate gas exchange. Currently available methods of ventilation do not account for the intermittent breathing strategy of representative species within this infraorder of fully aquatic mammals and may have a significant effect on cardiac and respiratory physiology. To understand the impact of mechanical ventilation on cardiopulmonary function in one small species of cetacean, the bottlenose dolphin (Tursiops truncatus), we compared controlled mechanical ventilation (CMV) to a novel ventilation method known as apneustic anesthesia ventilation (AAV). AAV simulates the normal inspiratory breath-hold pattern of dolphins. Ten anesthetic procedures (dental procedure, n = 9; bronchoscopy, n = 2) were performed on nine dolphins (age range: 10 -42 yrs; mean = 32 yrs; median = 37 yrs; female = 3, 40%; male = 6, 60%). In a cross-over study design, dolphins were instrumented and randomly assigned to AAV or CMV as the initial mode of ventilation, then switched to the alternate mode. Baseline cardiopulmonary data were collected and again after 30 minutes on each mode of ventilation. Cardiac index, stroke volume index, systemic vascular resistance, alveolar dead space, alveolar-arterial oxygen tension gradient, arterial oxygen content, oxygen delivery index, and dynamic respiratory system compliance index were calculated at each of the four time points. During AAV, dolphins had higher arterial oxygen tension, higher mean airway pressure, reduced alveolar dead space ventilation and lower alveolar-arterial oxygen difference. Cardiovascular performance was not statistically different between the two modes. Our study suggests AAV, which more closely resembles the conscious intermittent respiratory pattern phenotype of dolphins, improves ventilation and pulmonary function in the anesthetized dolphin. Future studies should evaluate the cardiopulmonary effects of neutral buoyancy and cardiopulmonary sparing drug protocols to reduce the need for hemodynamic support of current protocols.